Pengaruh Influencer dan E-Wom terhadap Minat Beli Konsumen pada Produk N’pure di Tangerang Selatan dengan Brand Trust Sebagai Variabel Intervening - Nabila Fitri (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This research discusses the influence of Influencers and eWOM on consumer buying interest in N'pure products in South Tangerang with Brand Trust as an intervening variable. Nowadays, the biggest purchases are made online through e-commerce and people look for references through social media. Influencers are familiar figures among social media users. Influencers who are honest will always be more trusted by their followers. That way, whatever the influencer recommends, their followers tend to be interested in that product. Coupled with positive reviews and ratings on e-commerce, it will increase consumers' trust in a product which can increase interest in purchasing a product. The aim of this research is to review and find out how influential influencers and eWOM are on consumer buying interest, using brand trust as an intervention. This research uses quantitative methods with a questionnaire survey with a total of 60 respondents. From the results of this research, it can be seen that influencers have an influence on increasing the Brand Trust of a product and eWOM has a great influence on consumer buying interest. Brand Trust has a positive effect on Purchase Intention. Even though Influencers are not significant in influencing Purchase Interest, increasing trust in the brand will make a product brand known to many people, in other words it will influence consumer purchasing interest.